7.9.21 problem 43

Internal problem ID [269]
Book : Elementary Differential Equations. By C. Henry Edwards, David E. Penney and David Calvis. 6th edition. 2008
Section : Chapter 2. Linear Equations of Higher Order. Section 2.2 (General solutions of linear equations). Problems at page 122
Problem number : 43
Date solved : Monday, January 27, 2025 at 02:43:09 AM
CAS classification : [_Gegenbauer]

\begin{align*} \left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y&=0 \end{align*}

Using reduction of order method given that one solution is

\begin{align*} y&=x \end{align*}

Solution by Maple

Time used: 0.005 (sec). Leaf size: 25

dsolve([(1-x^2)*diff(y(x),x$2)-2*x*diff(y(x),x)+2*y(x)=0,x],singsol=all)
 
\[ y = \frac {c_2 \ln \left (x -1\right ) x}{2}-\frac {c_2 \ln \left (x +1\right ) x}{2}+c_1 x +c_2 \]

Solution by Mathematica

Time used: 0.020 (sec). Leaf size: 33

DSolve[(1-x^2)*D[y[x],{x,2}]-2*x*D[y[x],x]+2*y[x]==0,y[x],x,IncludeSingularSolutions -> True]
 
\[ y(x)\to c_1 x-\frac {1}{2} c_2 (x \log (1-x)-x \log (x+1)+2) \]